New Approaches to Improvement of Ecological Activity Efficiency of Energy Sources - V. P. Bubnov; E. M. Minchenko; S. S. Deshits (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Development of power engineering significantly determines the level of the modern society. However, side by side with positive factors there are also negative ones. These negative factors are especially observed in the case of organic fuel usage. As a result of it the environment is polluted with hazardous emissions. Thus power engineering largely becomes dependent on not only economic factors but ecological ones as well.The paper proposes to assess efficiency of ecological activity of power sources with the help of international standards (14000 ISO), in other words it is recommended to introduce environment monitoring system.